2022
DOI: 10.1007/s11669-021-00935-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Immiscibility and Thermodynamic Assessment of the Al2O3–TiO2–SiO2 System

Abstract: Phase equilibria in the TiO2–SiO2 system have been studied experimentally using DTA and SEM/EDX. The thermodynamic parameters for the TiO2–SiO2 system have been assessed considering new experimental data of the present work and from the literature. Moreover, the miscibility of the liquid in the Al2O3–TiO2–SiO2 system has been studied at 2013 K in air and shrinkage of the miscibility gap at 3.8 mol% Al2O3 has been demonstrated. The experimental data obtained in the present work and literature as well as the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…The quantitative diffraction analysis of samples NN 13 and 14 showed that the main phases in these samples were rutile (40 and 53 mol%, respectively), cristobalite (40 and 35 mol%, respectively), and quartz (20 and 12 mol%, respectively). These results agree with the available data on the phase equilibria in the TiO 2 –SiO 2 system 22 . The presence of quartz in the samples might be explained by the partial transformation of cristobalite during cooling of samples NN 13 and 14 at room temperature from the synthesis temperature 1573 K when the samples were extracted from the furnace after the synthesis.…”
Section: Methodssupporting
confidence: 91%
See 4 more Smart Citations
“…The quantitative diffraction analysis of samples NN 13 and 14 showed that the main phases in these samples were rutile (40 and 53 mol%, respectively), cristobalite (40 and 35 mol%, respectively), and quartz (20 and 12 mol%, respectively). These results agree with the available data on the phase equilibria in the TiO 2 –SiO 2 system 22 . The presence of quartz in the samples might be explained by the partial transformation of cristobalite during cooling of samples NN 13 and 14 at room temperature from the synthesis temperature 1573 K when the samples were extracted from the furnace after the synthesis.…”
Section: Methodssupporting
confidence: 91%
“…From Table 2, the obtained values of the SiO 2 activities in the TiO 2 -SiO 2 system were characterized by positive deviations from Raoult's law at 1973 K. One of the possible reasons for this may be related to the fact that, according to the phase diagram of the TiO 2 -SiO 2 system, 21,22 above 2046 K there exists the miscibility gap in the melt of the system under study. 21 Existence of this miscibility gap in the melt might explain why the SiO 2 activity values were higher than the SiO 2 mole fractions.…”
Section: Modeling Using the Gltasmentioning
confidence: 93%
See 3 more Smart Citations